Numerical investigations of crack initiation in impulse steam turbine rotors subject to thermo-mechanical fatigue - Banaszkiewicz, Mariusz (Applied thermal engineering, 2018)
•Elastic and elastic-plastic finite element analyses done to study rotors cracking.•Heat grooves are the most critical areas from the viewpoint of thermal fatigue.•Predicted crack areas and number of cycles well correspond with inspections results.•Stress-strain correction rules provide lower and upper bound limits of fatigue life. The study presents the analysis of non-stationary stresses and fatigue cracking in impulse steam turbine rotors. Field experience with cracking of rotors is reviewed, and the most frequent crack locations are identified based on the same. Mathematical models of heat transfer and material constitutive behaviour used in numerical calculations of an intermediate pressure rotor are discussed. Calculations were performed with the help of finite element method for typical transient events including cold, warm, and hot start-ups and a shutdown. The highest stress and strain amplitudes were obtained in the heat grooves of a balance piston in which cracks were often observed during non-destructive testing. The number of cycles to crack initiation calculated based on the strain amplitudes correspond well with the operating experience of this type of rotors.